2012
DOI: 10.4321/s1130-01082012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Drawing up an individual risk index for development of metachronous neoplastic lesions in resected colorectal cancer

Abstract: Aim: to identify possible risk factors for the development of metachronous lesions in colorectal cancer (CRC) which would allow to establish a post-surgical individual prognostic index.Patients and methods: three hundred eighty-two surgically treated CRC were reviewed. We compared the incidence of metachronous lesions in 40 variables concerning patient clinical data and initial neoplastic findings. An individual risk index for metachronicity was drawn up including those variables which presented significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This is supported by previous studies which have also demonstrated that both MA and metachronous cancer occur more frequently in patients with a proximal tumour [ 24 , 25 ]. A more recent study, however, has challenged this view by describing a higher rate of MAs in patients with distal tumours and postulated that removal of the right colon protects against development of MAs which usually occur proximal to the primary cancer [ 26 ]. The observed association between proximal tumours and adenomas was previously believed to arise from cases with undiagnosed HNPCC and microsatellite instability (MSI) who are more likely to present with multiple lesions [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies which have also demonstrated that both MA and metachronous cancer occur more frequently in patients with a proximal tumour [ 24 , 25 ]. A more recent study, however, has challenged this view by describing a higher rate of MAs in patients with distal tumours and postulated that removal of the right colon protects against development of MAs which usually occur proximal to the primary cancer [ 26 ]. The observed association between proximal tumours and adenomas was previously believed to arise from cases with undiagnosed HNPCC and microsatellite instability (MSI) who are more likely to present with multiple lesions [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed the difference between patients with colon cancer and rectal cancer, and identified a difference between patients with right-sided and left-sided colon cancer. Studies have indicated that the risk for metachronous colorectal tumors is higher in patients with right-sided colon cancer than in those with left-sided colon cancer;16,35,36 how-ever, other studies have indicated that patients with left-sided colon cancer have higher risk 37,38. Based on a detailed classification of primary CRC subsites in the present study, the risk of multiple primary cancers gradually decreased from patients with right-sided colon cancer to those with left-sided colon cancer and to rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…47 There were 93 (1.8%) metachronous cancers diagnosed between 7 and 356 months after the initial CRC diagnosis (40.8% diagnosed within 36 months), and these were attributed to missed lesions in 43%, nonadherence to surveillance recommendations in 43%, and incomplete resection in 5.4%; de novo cancers accounted for only 5.4%. Several studies show that patients with CRC and synchronous adenomas or advanced adenomas have a higher risk of developing metachronous adenomas 12,40,42,46,[55][56][57][58][59] and advanced neoplasms, including cancer 40,[56][57][58][59][60][61] after surgery, underscoring the importance of adequate perioperative colonoscopy. The role of CTC in the perioperative setting is discussed in the section "Alternatives and Adjuncts to Colonoscopy," but the case of obstructive CRC precluding preoperative colonoscopy and perioperative clearing done by CTC deserves additional comment.…”
Section: Colonoscopy and Perioperative Clearing In Patients With Cancmentioning
confidence: 99%